The science of wastewater - Spellman, Frank R. (DEStech Publications, 2016)
"The scientific properties of different types of wastewater and the unit processes used to transform it into effluent of sufficient quality to be returned to the environment are explained in this comprehensive text. The book presents detailed descriptions of, and mathematical formulas for, wastewater treatment processes-from?dirty? influent to drinking-water-quality discharge. Operations include: filtering and activated sludge, detention basins, ponds and lagoons, and the stabilization and composting of biosolids."--Publisher's website
Keywords: Sewage -- Purification.; elektronické knihy; electronic books